Economics, organization, and management - Milgrom, Paul R. 1948- (Prentice-Hall, 1992)
A systematic treatment of the economics of the modern firm, this book draws on the insights of a variety of areas in modern economics and other disciplines, but presents a coherent, consistent, innovative treatment of the central problems in organizations of motivating people and coordinating their activities.